Barrier Coverage of Employment Social Security in the Agricultural Sector - Sucihatiningsih Dian Wisika Prajanti; Christina Litaay; Talitha Widiatningrum; Dhea Rizky Amelia (Sekolah Tinggi Ekonomi dan Bisnis Islam Lampung, 2023)
Agricultural sector workers are considered to have a lack of awareness and cost-complexities in accessing social security programs. The discussion of this study will focus on efforts to explore issues regarding the factors that influence the tendency or opportunity for workers to become participants in employment social security. Using the logistic regression method and Sakernas data 2019, it is found that agricultural workers with wages above the Regional minimum wage (UMR), workers who already have Health Social Security, formal agricultural workers, those living outside Java, farmers with monthly wages and heads of households tend to be more to become participants in employment social security. Recommendations for expanding participation for agricultural sector workers can be made with several alternatives, such as, (1) justifying or adjusting payment schemes for those who work with seasonal and uncertain wages. (2) To push the expansion of the scope of workers in the agricultural sector, Social Security Administrator for Employment/ BPJS Ketenagakerjaan can conduct program socialization in collaboration with the Social Security Administrator for Health/ BPJS Kesehatan. This is done since the participation of agricultural sector workers in the BPJS healthcare program is relatively high, (3) It is necessary to encourage employers in the agricultural sector to register their workers in social security, through an approach that is adjusted to the income pattern of farmers (seasonal).